Self Regulated Learning (SLR) as a Strategy to Build Student Independence - Zakiyah BZ; Putri Isnaini Hidayah; Hasan Baharun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to analyze the application of self-regulated learning as a strategy to build student independence by using several approaches to improve students' independent learning abilities in tertiary institutions. This research uses a qualitative case study approach. Data were obtained from interviews, observation, and documentation. Data analysis was conducted: collection, reduction, data display, and concluding. The results of the study show that self-regulated learning as a strategy for building student independence shows findings of varied approaches, namely, community-based learning, where learning involves student participation starting from planning, implementation and evaluation, e-resource management which directs students to be independent in finding information and learning resources through various electronic sources, and motivation to learn in order to achieve the targets to be achieved.